The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1158/0008-5472.can-07-2967
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Radioimmunotherapy from the Tumor Microenvironment of Colorectal Carcinomas

Abstract: Solid tumors have a heterogeneous pathophysiology, which directly affects antibody-targeted therapies. Here, we consider the influence of selected tumor parameters on radioimmunotherapy, by comparing the gross biodistribution, microdistribution, and therapeutic efficacy of either radiolabeled or fluorescently labeled antibodies (A5B7 anti-carcinoembryonic antigen antibody and a nonspecific control) after i.v. injection in two contrasting human colorectal xenografts in MF1 nude mice. The LS174T is moderately/po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 29 publications
5
84
0
Order By: Relevance
“…Limitations in antibody diffusion within solid tumour masses have previously been reported for reagents used in the IgG format (Adams and Weiner, 2005;Dennis et al, 2007;El Emir et al, 2007a), mainly in relation to the so-called 'antigen barrier'. In this study, we have used antibodies in SIP format (Borsi et al, 2002;Villa et al, 2008), as this format and similar mini-antibody formats have extensively been shown to offer distinctive advantages both for imaging applications (Leyton et al, 2009);von Lukowicz et al, 2007;Wei et al, 2008) and for radioimmunotherapy of cancer (Berndorff et al, 2005;Tijink et al, 2006;Kenanova et al, 2007;Sauer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations in antibody diffusion within solid tumour masses have previously been reported for reagents used in the IgG format (Adams and Weiner, 2005;Dennis et al, 2007;El Emir et al, 2007a), mainly in relation to the so-called 'antigen barrier'. In this study, we have used antibodies in SIP format (Borsi et al, 2002;Villa et al, 2008), as this format and similar mini-antibody formats have extensively been shown to offer distinctive advantages both for imaging applications (Leyton et al, 2009);von Lukowicz et al, 2007;Wei et al, 2008) and for radioimmunotherapy of cancer (Berndorff et al, 2005;Tijink et al, 2006;Kenanova et al, 2007;Sauer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…administration in the tail vein, we used both fluorescence microscopy and radioactivity-based detection methods. As mouse models of human cancer, we chose LS174T and SW1222 tumours: two colorectal cancer models, which have previously been extensively studied using monoclonal antibodies specific to the carcinoembryonic antigen (El Emir et al, 2007a;Fidarova et al, 2008) and with the vascular-targeting anti-EDB antibody L19 (El-Emir et al, 2007b). Figure 6 shows representative results of a multi-colour fluorescence microscopy analysis of serial sections from LS174T tumours, following i.v.…”
Section: A3 and Cc7 Selectively Target Hypoxic Tumour Regions In Vivomentioning
confidence: 99%
“…Although we did not have a nonspecific radiolabeled antibody ( 131 I-IgG1/MOPC) control in our studies, we have previously shown no therapeutic effect with a dose of 4 MBq of 131 I-IgG1/ MOPC in SW1222 tumor metastases (16), suggesting that cross-fire irradiation from circulating antibody does not significantly affect tumor growth. Moreover, our current studies show that 10 d after administration, the tumor-to-blood ratio of huA5B7 is approximately 8:1 in SW1222 tumors with minimal blood levels, which supports the hypothesis that the observed therapeutic effects were due to tumor-bound antibody rather than circulating antibody.…”
Section: Discussionmentioning
confidence: 96%
“…HuA5B7 was provided by UCB Pharma S.A. and labeled with 131 I ( 131 I-huA5B7) (Perkin Elmer, U.K.) using the IODO-GEN (Pierce) method as previously described (16,17). Labeling yield and radiochemical purity were assessed by thin-layer chromatography (silica gel Si60, stationary phase; 80% methanol, mobile phase); antigen binding of the radiolabeled antibody was compared with nonlabeled huA5B7 and assessed by enzyme-linked immunosorbent assay.…”
Section: Agents and Antibody Labelingmentioning
confidence: 99%
See 1 more Smart Citation